2002
DOI: 10.1086/339815
|View full text |Cite
|
Sign up to set email alerts
|

Age at Onset in Two Common Neurodegenerative Diseases Is Genetically Controlled

Abstract: To identify genes influencing age at onset (AAO) in two common neurodegenerative diseases, a genomic screen was performed for AAO in families with Alzheimer disease (AD; n=449) and Parkinson disease (PD; n=174). Heritabilities between 40%--60% were found in both the AD and PD data sets. For PD, significant evidence for linkage to AAO was found on chromosome 1p (LOD = 3.41). For AD, the AAO effect of APOE (LOD = 3.28) was confirmed. In addition, evidence for AAO linkage on chromosomes 6 and 10 was identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
229
2
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(251 citation statements)
references
References 34 publications
17
229
2
3
Order By: Relevance
“…However, Li et al [14,40] argued that the age-atonset of disease is equally important because the "regulation of onset could make it possible to delay onset beyond an individual's normal life span." Indeed, allelic variation in APOE profoundly affects risk by lowering the age-at-onset of AD between three to five years with each copy of the ε4 variant [6,8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Li et al [14,40] argued that the age-atonset of disease is equally important because the "regulation of onset could make it possible to delay onset beyond an individual's normal life span." Indeed, allelic variation in APOE profoundly affects risk by lowering the age-at-onset of AD between three to five years with each copy of the ε4 variant [6,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, analyses using age-at-onset of disease as a quantitative trait have yielded multiple putative loci on chromosomes 2, 7, 9, 14, 15, 20 and 21, and some of these loci were also found to be significant in the analyses of AD phenotype [13][14][15][16][17][18][19]. However, most of these analyses lack independent confirmation, with the exception of the locus at 14q32 [16] which is of interest because of its location near PSEN 1.…”
Section: Introductionmentioning
confidence: 99%
“…Identified by linkage of a population-based register of PD patients and a nation-wide genealogical database in Iceland, these families had typical PD with average age of onset 66 years. The PARK10 locus was also linked to age at onset for PD in a US sample [248]. Association between SNPs in the candidate gene ELAVL4 and age at onset for PD or susceptibility to PD were reported in Caucasian populations [249][250][251], but have not been confirmed in other populations.…”
Section: Park10mentioning
confidence: 94%
“…Linkage studies have identified several promising chromosomal regions to harbor additional AD genes, including chromosomes 12, 10, 9 and 6 [reviewed in 7]. A broad linkage peak encompassing >60 cM region between chromosome 10q21 and 10q25 that influence both AD risk and AAO has been suggested [2,4,10,13]. There are more than 300 genes in this broad genomic region of chromosome 10 and thus the task of identifying the chromosome 10 candidate gene is daunting.…”
Section: Introductionmentioning
confidence: 99%